2022
DOI: 10.3390/jcdd9080255
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Mortality Risk in Patients with Bladder Cancer: A Population-Based Study

Abstract: Background: The purpose of this study was to evaluate the risk of cardiovascular mortality (CVM) among patients with bladder cancer (BC). Methods and Materials: Data were collected from the Surveillance, Epidemiology, and End Results (SEER) database for patients who were diagnosed with BC by pathology between 2000 and 2016. The standardized mortality rate (SMR) was calculated based on reference data from the general population. Nelson–Aalen cumulative hazard curves were used to assess the risk of experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Although we were unable to eliminate all potential confounding variables completely, we did our best to validate the study results. Similar to earlier reports, [ 18 , 29 ] our investigation highlights a noteworthy decline in CVM susceptibility among cancer survivors who underwent surgery compared to their nonsurgical counterparts. Our results provide strong evidence indicating a link between CVM risk and tumor resection, further reinforcing the conclusion that resecting the primary tumor reduces the risk of CVM in cancer survivors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although we were unable to eliminate all potential confounding variables completely, we did our best to validate the study results. Similar to earlier reports, [ 18 , 29 ] our investigation highlights a noteworthy decline in CVM susceptibility among cancer survivors who underwent surgery compared to their nonsurgical counterparts. Our results provide strong evidence indicating a link between CVM risk and tumor resection, further reinforcing the conclusion that resecting the primary tumor reduces the risk of CVM in cancer survivors.…”
Section: Discussionsupporting
confidence: 91%
“…Although we were unable to eliminate all potential confounding variables completely, we did our best to validate the study results. Similar to earlier reports, [18,29] our investigation highlights a noteworthy decline in CVM susceptibility among cancer survivors who underwent surgery compared to their nonsurgical counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with recent studies reporting increased CVD risk in bladder cancer, osteosarcoma, gallbladder cancer, colorectal cancer, and lymphoma. [ 25 , 30 , 46 48 ] Although the SMR was lowest in the elderly group, it was still higher 7 th an in the general elderly population. The reason for the higher SMR in the elderly group may be attributed to their poorer health, reduced immunity, and increased prevalence of comorbidities, including infections.…”
Section: Discussionmentioning
confidence: 93%
“…This trend may be attributed to the current advancements in treatment strategies for HCC patients, as well as the improved treatment and emergency measures for CVDs, as previously reported in the literature. [27–30] Additionally, our study identified age, tumor differentiation, tumor size, surgical status, and SEER stage as independent predictors of CVD in patients with HCC. These findings suggest that cardiovascular disease staging of HCC patients should be done in advance in the treatment and care of HCC patients in order to develop a rational therapeutic regimen thereby reducing the risk of cardiovascular mortality and improving the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer as one of the most common malignancies in urology, patients are often more concerned about BC-related mortality. However, due to continuous medical advances and developments, the overall survival of BC patients has been effectively improved(Richters et al 2020 ; Lenis et al 2020 ; Marrie et al 2021 ), leading to the prominence of deaths from non-cancer diseases (Wang et al 2022a ).…”
Section: Discussionmentioning
confidence: 99%